Nanocomposite-based packaging affected the taste components of white Hypsizygus marmoreus by regulating energy status. (1st May 2020) - Yan, Ming; Yuan, Biao; Cheng, Shujie; Huang, Huidan; Huang, Dechun; Chen, Jianqiu; Cao, Chongjiang
Highlights: Nano-PM reduced the loss of taste components of postharvest white Hypsizygus marmoreus. Nano-PM maintained ATP content and energy charge by keeping the ATPase activities. Nano-PM delayed the mitochondrial microstructure breakdown to maintain higher energy status. A potential mechanism described for flavor quality preservation with Nano-PM. Abstract: The effects of nanocomposite-based packaging material (Nano-PM) on the taste components and mitochondrial energy metabolism of postharvest white Hypsizygus marmoreus (WHM), as well as the underlying influence mechanism were investigated. The results showed that the major taste components, including succinic acid and mannitol, remained at higher level in Nano-PM. The flavor 5′-nucleotides (5′-GMP and 5′-IMP) of WHM in Nano-PM were significantly higher ( p  < 0.05) compared with that in the normal packaging material (Normal-PM). Principal component analysis indicated that there was a distinction of flavor compounds (6 organic acids, 3 soluble sugars and 5 5′-nucleotides) of WHM between Nano-PM and Normal PM treatments during storage. Moreover, Nano-PM delayed the mitochondrial microstructure breakdown and the reduction of ATPase activity, and it maintained a higher ATP content and higher level of energy charge. Our results demonstrated that Nano-PM could affect the taste components of postharvest WHM partially by regulating the energy metabolism.